The Effect of Liquidity, Profitability, Leverage on Corporate Value with Dividend Policy and BI Rate as Moderated Variables (Study of Banking Companies Listed on the Indonesia Stock Exchange in 2014-2017) - Setiawan, Dana Eka; Rahmawati, Ika Yustina (Economics and Business Solutions Journal, 2020)
This study aims to examine the effect of liquidity, profitability, leverage on corporate value with dividend policy and the BI Rate as a moderating variable on banking companies listed on the Indonesia Stock Exchange in 2014-2017. The study used a purposive sampling method for sampling, as many as 13 banks based on criteria. This study uses secondary data from company annual reports. Data were analyzed using SPSS 25. The results showed that: liquidity had a negative and not significant effect on corporate value, profitability had a positive and significant effect on corporate value, leverage had a negative and not significant effect on corporate value, dividend policy and the BI Rate are not able to moderate the effect of liquidity, profitability, and leverage on corporate value.